Assessment of Rock Masses Exposed at the Khanas Dam Site in the Southeastern Part of Sheikhan Anticline, Northern Iraq. (Iraqi National Journal of Earth Science (INJES), 2026)
This study is based on assessing rock masses exposed on the banks of the Khanas Dam reservoir in the southeastern part of the Sheikhan Anticline in northern Iraq. The rock masses are of the Pila Spi Formation. The study includes field data, laboratory tests, and office work. During the study, seven stations were chosen and distributed on both banks, four stations on the right and three stations on the left, considering that the Pila Spi Formation is the dominant and representative geological formation of the study area, and it represents the foundation of the dam, Shoulders, and banks overlooking the reservoir. The rock masses of the Pila Spi Formation are represented by limestone, chalky limestone, and dolomitic limestone as a result of the diagenetic process. Three classifications are used to assess rock masses: Rock Mass Rating (RMR), Dam Mass Rating (DMRSTA), and Geological Strength Index (GSI). As a result of the classification of rock masses, they range between (50-61) on the right bank, while on the left bank, they range between (53-62). The results of the assessment of the stability of the Dam Mass Rating on the right bank range between (61-66), while on the left bank range between (58-67). The results of the geological strength index values for rock mass on the right bank are between 41-56, while the results on the left bank are between 48-57. The Roclab program was also used, through which the mechanical properties of rock masses, represented by cohesion strength(C) and angle of internal friction(Ø), are determined using the Hoek-Brown failure criterion. Cohesion strength on the right bank range is between (0.362-0.877MPa), while on the left bank, their values range between (0.385-0.869MPa). The angle of internal friction on the right bank ranges between (24.26°-28.15°), while on the left bank, the values range between (25.31°- 28.51°).
Keywords: Rock Mass Rating Dam Mass Rating Geological Strength Index Khanas Dam Banks of the Dam